Staging the Iberian Moor in Thomas Colley Grattan’s Ben Nazir, The Saracen (1827): Gaps, Incongruities and Failure in Discursive Orientalism - El idrissi, Zakariae (International Journal of Language and Literary Studies, 2023)
Going beyond Edward Said’s discursive coherence and internal consistency, this paper analyses Thomas Colley’s Ben Nazir, The Saracen (1827) to illustrate the internal inconsistency, discursive incoherence, plurality, and complexity of Moorish-themed Orientalism. Unlike Edward Said’s logic of monolithism and his notion of exteriority that he detailed mainly in his Orientalism, some critics, such as Lisa Lowe, Dennis Porter, Sara Mills, Peter Hulme, and Ali Behdad, to name but a few prominent critics, focus on the subtext, the hidden, and the non-said in order to transcend western hegemony, textual centrality, and fixed representation and stress the asymmetrical subversive practices that uncover discursive heterogeneities, contradictions, and slippages of authorial control. So, by exploring and adding to their productions, my reading of Ben Nazir would reveal how the representation of the Spanish Moor may be turned from a site of productive power into a site of subversive knowledge and how discursive statements may be fractured by their own gaps, silences, and incongruities. In my analysis, I argue that Colley’s intention to discursively denigrate the Moor while ennobling the Christian is subversively thwarted by aesthetic demands, considerably disturbed by counter-ideologies and histories, and persistently challenged by dramatic dialogism.